Comprehensive Evaluation of Ecological Sensitivity and the Characreristics of Spatial Variations in Luo River Basin - Yu, Yang; Yuan, Mingyang (International Journal of Natural Resources and Environmental Studies, 2026)
This study focuses on the Luo River Basin in Henan Province, selecting six ecological evaluation factors—elevation, slope, land use, NDVI, aspect, and water buffer zone—to assess ecological sensitivity. The Analytic Hierarchy Process (AHP) and spatial autocorrelation analysis were employed to determine the weights and spatial distribution of each factor. Based on the GIS platform, comprehensive ecological sensitivity was classified into five levels, facilitating an integrated analysis of sensitivity distribution and spatial autocorrelation clustering patterns in the Luo River Basin from 1990 to 2020. The results indicate: ① According to single-factor evaluations, the weights of ecological sensitivity influence, in descending order, are NDVI, land use, elevation, slope, aspect, and water buffer zone. Among these, NDVI exerts the strongest impact on ecological sensitivity in the Luo River Basin, with a weight value of 0.345.② From 1990 to 2020 the eco-environmental sensitivity of the study area was predominantly extremely high, followed by low and high sensitivity. Extremely high and high sensitivity areas together accounted for 42.32% to 51.45% of the total regional area, exhibiting an increasing trend over time, with the proportion of extremely high sensitivity areas reaching up to 32.27%. moderate and low sensitivity areas displayed a declining trend, while very low sensitivity areas remained relatively stable at approximately 16%.③ The spatiotemporal variations in ecological sensitivity within the study area are pronounced. Overall, extremely high and high sensitivity areas are primarily concentrated in the mountainous and hilly regions of the western and central-southern parts, characterized by high elevations and steep slopes. Very low and low sensitivity areas are mainly distributed near urban clusters in the eastern and central valley regions of the Luo River Basin. The ecological sensitivity index in the basin exhibits a zonal clustering pattern at the spatial scale, with clustering intensity fluctuating slightly over time but showing an overall increasing trend.